PENINGKATAN PENGETAHUAN IBU-IBU TENTANG BAHAN BERBAHAYA DALAM KOSMETIK DAN CARA MEMILIH PRODUK AMAN - Vica Aspadiah; Fery Indradewi Armadany; Erniyanti Erniyanti; Ratna Ratna; Anawula Mengga; Muhammad Faiz Almath; Wa Ode Musdalifa (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
The widespread use of cosmetics among women has increased the risk of exposure to hazardous ingredients due to the circulation of illegal products. This community service activity aimed to improve the knowledge of women in Bungkutoko Village, Nambo District, Kendari City, regarding hazardous substances in cosmetics and how to select safe products. The activity employed a participatory educational approach through lectures, interactive discussions, leaflet distribution, and pretest-posttest evaluations. Twenty participants attended the program. The results showed that before counseling, 70% of participants had a low level of knowledge. After the educational intervention, 70% of participants achieved a good level of knowledge. These findings indicate that the counseling program effectively increased community awareness and understanding regarding the importance of choosing safe and legal cosmetic products.